Evaluating ginger extract for controlling postharvest anthracnose of mango - Malek, Amirah (2016)
Colletotrichum gloeosporioides (Penz.) Sacc. (C. gloeosporioides) is a causal agent of anthracnose disease in many tropical fruit trees, especially mango trees. Therefore, ginger, (Zingiber officinale rosc) has been used as naturopathy due to their antimicrobial activity potential to inhibit the growth of different microbial pathogens. This study investigated the in vitro potential of antifungal activities of rhizome extract from Z. officinale rosc to control Colletotrichum gloeosporioides on post-harvest anthracnose of mango. In addition, the common use of chemical fungicides to manage anthracnose disease causes the development of fungal resistance. Hence, effective bio-control methods for managing anthracnose diseases were investigated. The effect of crude extracts obtained from Z. officinale rosc through ethanol and water extraction methods were tested against C. gloeosporioides. Both of these crude extracts were efficient in inhibiting the growth of C. gloeosporioides. However, ethanol was found to be most effective at concentration of 50%. Overall, a significant reduction in the growth of C. gloeosporioides was found to be associated with the plant extract tested.